The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1007/s12306-011-0110-2
|View full text |Cite
|
Sign up to set email alerts
|

Gap balancing versus measured resection technique using a mobile-bearing prosthesis in computer-assisted surgery

Abstract: Navigation has been developed to help surgeons install implants more accurately and reproducibly; at the same time, this tool is able to record quantitative information such as joint range of motion, laxity and kinematics intra-operatively. As for standard surgery, two strategies are possible to achieve either femoral component rotation or overall prosthetic alignment: a measured gap resection approach, in which bone landmarks are used to guide resections equal to the distal and posterior thickness of the femo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 17 publications
(21 reference statements)
0
19
0
1
Order By: Relevance
“…Joint line elevation caused by TKA is not uncommon; the incidence can reach 40% after primary TKA [ 13 , 36 38 ]. Kawamura and Bourne [ 39 ] reported a mean joint line elevation of 3.5 mm, Sabbioni et al [ 40 ] reported 4.0 mm, and Scuderi and Insall [ 41 ] reported 5.6 mm.…”
Section: Discussionmentioning
confidence: 99%
“…Joint line elevation caused by TKA is not uncommon; the incidence can reach 40% after primary TKA [ 13 , 36 38 ]. Kawamura and Bourne [ 39 ] reported a mean joint line elevation of 3.5 mm, Sabbioni et al [ 40 ] reported 4.0 mm, and Scuderi and Insall [ 41 ] reported 5.6 mm.…”
Section: Discussionmentioning
confidence: 99%
“…Sabbioni et al reported joint line elevation to be 4.09 mm in the GB technique and 3.50 mm in the MR technique using a posterior stabilized knee system. This change was significantly greater for GB knees (P ¼ .036) [44]. Tigani et al also compared the GB and MR techniques performed with CAS-TKA and found that although both led to joint line elevation, there was statistically greater elevation in GB knees (P ¼ .008) [19].…”
Section: Discussionmentioning
confidence: 98%
“…Compared with the tibial plateau, the bular head is independent of TKA, as well as osteophytes or the destruction of tibiofemoral articular surface. And the recognition of the styloid process of bular head is accurately acquired on the standard lateral radiograph [20,30]. In this study, the tibial shaft axis was determined by selecting two mid-diaphyseal points at 70-and 110-mm distal to the tibial plateau down the tibial shaft, in which could avoid an increase of the measurement variability, as described by previous studies [22,23].…”
Section: Discussionmentioning
confidence: 99%